The Burden of Culture - Vargas, M. (Handbook of International Relations: Issues of Human Rights And Foreign Policy - Vol. II, 2017)
The Burden of Culture: A Case Study on Cooperation, Racism and Foreign Policy Mojana Vargas Center for International Studies ISCTE-IUL, Portugal ABSTRACT This chapter presents the partial results of the research entitled "Educational Cooperation and Prestige Search in Brazilian Foreign Policy for African Portuguese Speaking Countries (2000-2010)”. The research was carried out based on the constructivist epistemology applied to Foreign Policy Analysis, in which Foreign Policy is a particular kind of Public Policy (Pinheiro; Salmón, 2013; Putnam, 1988). The results are based on analyze of data collected through application of questionnaires and semi-structured interviews with students from Cape Verde and Guinea-Bissau, about their experiences at Brazilian universities. The objective is discuss the effects of cultural differences on cooperation process as an instrument of foreign policy. It shows how the context of racial relations in Brazil affects Brazilian cooperation for development towards African countries and influences the external perception about the country.